Kandungan Iodium pada Garam Dapur di Pasar Batuah Martapura Maret 2014 - haitami haitami (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2015)
Abstract: Research on the content of iodine in salt Kitchen in the Market Martapura March 2014 aims to determine the iodine content in the salt that is sold in the market Batuah Martapura and look for compliance with quality standards ISO 01-3556.2-1994 / Rev 2000. The method used in this study is a descriptive survey. The sample used in this study is a salt-branded and not branded, with a total sampling technique sampling. The research found 67% salt containing KIO3, and 33% of salt that does not contain KIO3, KIO3 in salt levels ranged from 8.68 ppm - 79.94 ppm, 53% salt that does not qualify SNI and only 47% were eligible, 100% salt not branded ineligible SNI and 42% SALT branded ineligible SNI. The public to be cautious in buying salt consumption for everyday purposes, and to the relevant agencies to conduct outreach and firm action against violations that exist in society against the marketing of salt that does not comply with permitted.